MAKNA DAN FUNGSI SOSIAL BAHASA GAUL BETAWI ORA PADA REMAJA DI KOTA BEKASI: KAJIAN SOSIOLINGUISTIK - Mohammad Dharmansyah; Dian Karina Rachmawati; Idhoofiyatul Fatin (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2026)
Teenage slang is a dynamic linguistic variation that evolves alongside the intensity of social interaction in urban areas. In Bekasi City, teenage slang shows a strong tendency to absorb elements of the local Betawi Ora dialect, which then undergo adaptations in form and meaning to meet the speakers' communication needs. This study aims to describe the contextual meaning and social functions of Betawi Ora-based slang vocabulary used by teenagers in Bekasi City. This research employed a qualitative descriptive method with a sociolinguistic approach. Data were collected through participatory observation (SLC) and non-participatory observation (SBLC) involving 11 teenagers aged 18–22 years through three observation sessions conducted in public social spaces. The results identified 15 key vocabularies, including bagen, danta, ilok, sabi, and eug, whose meanings are highly dependent on the speech situation and the relationship between speakers. Findings indicate that these vocabularies serve multidimensional social functions: as group identity markers, means of emotional expression, solidarity-strengthening strategies, and conflict control mechanisms. This study confirms that local dialect elements continue to play a vital role in shaping the linguistic identity of the younger generation amidst urban social dynamics.